« Beautiful physiques, dizzying sex and exhilarating settings ». Production et reproduction des récits nationaux et des imaginaires homoérotiques dans les campings gais québécois - Lefebvre Morasse, Hugues (RACAR : Revue d'art canadienne / Canadian Art Review, 2025)
Men-only gay campgrounds in Quebec function as contested landscapes, resisting dominant ideological narratives surrounding queerness and its relation to nature. While operating as utopian refuges that challenge metronormativity, these sites reveal profound ambivalence. This article analyzes their visual and spatial cultures—from camp landscaping to pornographic archetypes—as practices of disidentification and world-making that redefine the figure of the camper and its environment. Situated within broader imaginaries of wilderness and national belonging, these enclaves deploy aesthetics of classical pastoralism and pornified hypermasculinity that both subvert heteronormativity and reproduce dominant colonial structures. By mobilizing the myth of terra nullius and homonationalist tropes such as the fetishized Mountie, these spaces materialize the enduring entanglement of desire, landscape, and ideology, ultimately exposing a critical tension between queer emancipation and colonial reproduction within Canadian visual and spatial narratives.